A noncompact variational problem in the theory of riesz potentials. II - Zorii, N. V. (Ukrains’kyi Matematychnyi Zhurnal, 1996)
We study some generalizations of the well-known problem of minimization of the Riesz energy on condensers. Under fairly general assumptions, we establish necessary and sufficient conditions for the existence of minimal measures.